Investigating the origins and evolution of a glyphosate‐resistant weed invasion in South America. Issue 21 (2nd November 2021) - Gaines, Todd A.; Slavov, Gancho T.; Hughes, David; Küpper, Anita; Sparks, Crystal D.; Oliva, Julian; Vila‐Aiub, Martin M.; Garcia, M. Alejandro; Merotto, Aldo; Neve, Paul
Abstract: The global invasion, and subsequent spread and evolution of weeds provides unique opportunities to address fundamental questions in evolutionary and invasion ecology. Amaranthus palmeri is a widespread glyphosate‐resistant (GR) weed in the USA. Since 2015, GR populations of A . palmeri have been confirmed in South America, raising questions about introduction pathways and the importance of pre‐ vs. post‐invasion evolution of GR traits. We used RAD‐sequencing genotyping to characterize genetic structure of populations from Brazil, Argentina, Uruguay and the USA. We also quantified gene copy number of the glyphosate target, 5‐enolpyruvyl‐3‐shikimate phosphate synthase ( EPSPS ), and the presence of an extrachromosomal circular DNA (eccDNA) replicon known to confer glyphosate resistance in USA populations. Populations in Brazil, Argentina and Uruguay were only weakly differentiated (pairwise F ST ≤0.043) in comparison to USA populations (mean pairwise F ST =0.161, range =0.068–0.258), suggesting a single major invasion event. However, elevated EPSPS copy number and the EPSPS replicon were identified in all populations from Brazil and Uruguay, but only in a single Argentinean population. These observations are consistent with independent in situ evolution of glyphosate resistance in Argentina, followed by some limited recent migration of the eccDNA‐based mechanism from Brazil to Argentina. Taken together, our results are consistent with an initial introduction of A . palmeri into South America sometime before the 1980s, and local evolution of GR in Argentina, followed by a secondary invasion of GR A . palmeri with the unique eccDNA‐based mechanism from the USA into Brazil and Uruguay during the 2010s.